Factors Cause of students’ Anxiety in Speaking Ability in Speech at STIKes Paluta Husada - Yulina Oktaviani Harahap; Yulinda Oktaviana Harahap (International Journal of Educational Research Excellence (IJERE), 2024)
Speaking is one of the most critical language skills that English language learners must develop. However, not all students can communicate in English. Students find it difficult to communicate themselves in speech, and they have encountered a variety of obstacles.The purpose of this study is to determine the factors that generate students' anxiety in speech, as well as the link between students' speaking skill in speech and their degree of anxiety. This study employed descriptive research. The study included 28 midwifery students from STIKes Paluta Husada throughout the course of six semesters. The data suggest that communication apprehension, fear of poor assessment, and exam anxiety were the elements that caused students' nervousness when making a speech.